(untitled) - SUHARTATIK, NUR (Jurnal Ilmu Manajemen (JIM), 2013)
Financing to Deposit Ratio (FDR) is the ratio between thefinancing provided by bank to the third party.The purpose of this studywas to analyze the effect of the Capital Adequacy Ratio (CAR), ThirdParty Funds (TPF), Bank Indonesia Sharia Certificate (SBIS), NonPerforming Financing (NPF) of the Financing to Deposit Ratio (FDR).The method used is the purposive sampling method. With dataanalysis techniques multiple linear regression. Hypothesis testingusing t-statistics and F-statistics.Results showed that the independentvariables simultaneosly influence the FDR. Partially, NPF influenceon FDR. While CAR, DPK, SBIS no effect on the FDR. So should thelevel of NPF stabil so as not to exceed the limit set by BI.Keywords: Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Third Party Funds (TPF), Bank IndonesiaSharia Certificate (SBIS), Non Performing Financing(NPF).